Environmental Molecular Effect on the Macroscale Friction Behaviors of Graphene - Li, Panpan; Wang, Bo; Ji, Li; Li, Hongxuan; Chen, Lei; Liu, Xiaohong; Zhou, Huidi; Chen, Jianmin (Frontiers in Chemistry, 2021)
The friction behaviour of graphene in air and nitrogen atmosphere environments are investigated. The microstructural evolution caused by the variation of the atmosphere environments and its effect on the friction coefficient of the graphene is explored. It is demonstrated that graphene can exhibit excellent lubricating properties both in air and nitrogen atmosphere environments. In air, a highly ordered layer-by-layer slip structure can be formed at the sliding interface. Oxygen and H2O molecules can passive the edge dangling bonds and defects. Thus the interaction between the nanosheets and the layers of nanosheets is weak and the friction coefficient is low (0.06-0.07). While the friction coefficient increases to 0.14-0.15 in nitrogen atmosphere due to the interaction of defects generated in the sliding process, and the nitrogen molecules with lone pair electrons only can passive the nanosheets in a certain degree, thus the ordered slip structure is destroyed and friction is higher. This work reveals the influence of environmental molecular on macroscale tribological performances of graphene and its effect on the microstructure at sliding interface, which could be shed light on the lubricating performance of graphene in environmental atmospheres and help to understand the tribological behaviours of graphite at macroscale.